2013
DOI: 10.1159/000354366
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Person-Centred Dementia Care to Prevent Agitation and Other Neuropsychiatric Symptoms and Enhance Quality of Life in Nursing Home Patients: A 10-Month Randomized Controlled Trial

Abstract: Aims: We examined whether Dementia Care Mapping (DCM) or the VIPS practice model (VPM) is more effective than education of the nursing home staff about dementia (control group) in reducing agitation and other neuropsychiatric symptoms as well as in enhancing the quality of life among nursing home patients. Methods: A 10-month three-armed cluster-randomized controlled trial compared DCM and VPM with control. Of 624 nursing home patients with dementia, 446 completed follow-up assessments. The primary outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(155 citation statements)
references
References 86 publications
(66 reference statements)
4
147
2
2
Order By: Relevance
“…The participants were recruited from the research project Effects and costs of a day care centre program designed for people with dementia -a 24 month controlled study (ECOD) (Rokstad et al, 2013). The sample from the ECOD study, which this PhD study has recruited participants from, was a strategic sample that consisted of 175 participants who represented the intervention group, i.e.…”
Section: Samplementioning
confidence: 99%
“…The participants were recruited from the research project Effects and costs of a day care centre program designed for people with dementia -a 24 month controlled study (ECOD) (Rokstad et al, 2013). The sample from the ECOD study, which this PhD study has recruited participants from, was a strategic sample that consisted of 175 participants who represented the intervention group, i.e.…”
Section: Samplementioning
confidence: 99%
“…Dementia Care Mapping (DCM) is a widely used method to support staff working in dementia care in psychogeriatric nursing homes (Barbosa, Lord, Blighe, & Mountain, 2017;Chenoweth et al, 2009;Jeon et al, 2012;Kuiper, Dijkstra, Tuinstra, & Groothoff, 2009;Rokstad et al, 2013;Van de Ven, 2014). It is promising for staff working with older people with intellectual disability and has a number of characteristics that are innovative for this field: it is a relatively structured psychosocial method, it is based on principles of person-centred care, and it is specifically aiming at people with dementia (Finnamore & Lord, 2007;Jaycock, Persaud, & Johnson, 2006;Persaud & Jaycock, 2001;Schaap, Dijkstra, Finnema, & Reijneveld, 2017).…”
mentioning
confidence: 99%
“…There is a wide range of approaches to person-centred care, the minority of which have an evidence base. Dementia care mapping 216,217,237 is a particular approach that is reported to be time-consuming and expensive compared with other forms of PCC but achieves equivalent or improved outcomes for residents in care homes. 216 The majority of person-centred care research among PLWD in care homes focuses on outcomes, such as quality of life, activities of daily living and behavioural symptoms such as agitation.…”
Section: Summary Of Scoping Findingsmentioning
confidence: 99%
“…Rokstad et al 237 reported that professional leadership facilitated staff engagement with PCC awareness and practice, whereas market approach and traditional approach did not give a clear vision or commitment to professional development. This was a small study (only three care homes participated), but it addresses how leadership style influences uptake of PCC and also draws a link with outcomes and funding and care home organisation.…”
Section: Implementation In Care Homesmentioning
confidence: 99%